Identifying priority villages for wildfire mitigation based on exposure and vulnerability levels at the local scale - Oliveira, Sandra (2023)
This study aimed to assess wildfire risk specifically for human settlements, testing the procedure in three regions of mainland Portugal, representing the west coast (Oeste), the south coast (Algarve) and a central inland sector (Viseu-Dão-Lafões).